The Concept of Nature and the Development of Human Potential in Islamic Education Based on Surah An-Nahl verse 78 - Khairunissa Alya Br. Solin; Sarwadi Sulisno (Aslim: Journal of Education and Islamic Studies, 2025)
Surah An-Nahl verse 78 outlines the fundamental concept of human nature (fitrah) as a learning being. The verse emphasizes that humans are born without knowledge, yet Allah equips them with three essential faculties for learning and self-development: hearing (as-sam‘u), sight (al-abṣār), and the heart or intellect (al-af’idah). These capacities form the epistemological foundation of Islamic education, which highlights the holistic use of human faculties in the pursuit of knowledge and truth. In Islamic educational thought, learning is not merely a cognitive activity but also a spiritual process, with gratitude as its ultimate objective. This article examines the concept of fitrah and the development of human potential in Islamic education based on Surah An-Nahl verse 78 through a library research approach. The findings indicate that Islamic education is an integrative process of cultivating human consciousness by directing sensory, intellectual, and spiritual potentials toward noble character and the common good.